2014
DOI: 10.1021/ie501678j
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Interface Chemistry to Improve the Strength of Carbon Fiber Composites Cured by Electron Beam

Abstract: A reactive sizing was designed to achieve high levels of interfacial adhesion and improved mechanical properties with a carbon fiber–acrylate system cured by electron beam (EB). The sizing was made of a partially cured epoxy sizing with a high density of pendant functional groups (acrylate functionality) to facilitate covalent bonding with the matrix. The interlaminar shear strength improved from 61 to 81 MPa (+33%) without postprocessing, reaching a shear strength similar to that of the same system cured by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…[10][11][12] To reinforce the interface of CFRP, CF surface need to be modified. In recent decade, many methods to improve the interfacial adhesion of fibrous composites have been proposed, such as chemical grafting, [4,12,13] sizing, [7,14,15] growing carbon black, [10,16,17] electrophoretic deposition, [18][19][20] and introducing nanoparticles. [21][22][23][24][25] But some of them are carried out at extremely toxic, high-energy consuming and harsh conditions, which have a limited development in industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] To reinforce the interface of CFRP, CF surface need to be modified. In recent decade, many methods to improve the interfacial adhesion of fibrous composites have been proposed, such as chemical grafting, [4,12,13] sizing, [7,14,15] growing carbon black, [10,16,17] electrophoretic deposition, [18][19][20] and introducing nanoparticles. [21][22][23][24][25] But some of them are carried out at extremely toxic, high-energy consuming and harsh conditions, which have a limited development in industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Consequently, the generation of physical and chemical interactions leads to a high adhesion in the interphase. In a recent study, [11] EB curing was successfully used to improve the mechanical properties of carbon fiber acrylate composites. Consequently, the low-molecular and low-modulus components of the sizing act as softener and the improvement in interfacial adhesion is limited in comparison to thermosets.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to chemical agents, the generation of chemical reactive species is free of low-molecular unreacted products acting as softener as well. In a recent study, [11] EB curing was successfully used to improve the mechanical properties of carbon fiber acrylate composites. In the case of PP, free radicalinduced chemical reactions are well studied and lead to a degradation of PP and reduced mechanical performance.…”
Section: Introductionmentioning
confidence: 99%
“…The sizing was made of a partially cured epoxy sizing with a high density of pendant functional groups (acrylate functionality) to facilitate covalent bonding with the matrix. The experiment results showed that the interlaminar shear strength improved from 61 to 81 MPa (+33%) without postprocessing, reaching a shear strength similar to that of the same system cured by a thermal treatment [9]. This constitutes a breakthrough for the industrial development of EB curing of composites [9].…”
Section: The Applications Of Cfcmsmentioning
confidence: 71%
“…Recently, a carbon fiber-acrylate system cured by electron beam (EB) was designed to achieve high levels of interfacial adhesion and improved mechanical properties by a reactive sizing [9]. The sizing was made of a partially cured epoxy sizing with a high density of pendant functional groups (acrylate functionality) to facilitate covalent bonding with the matrix.…”
Section: The Applications Of Cfcmsmentioning
confidence: 99%